Вплив конструктивно-технологічних параметрів робочих органів глибокорозпушувача на тяговий опір - Лещенко, С. М.; Сало, В. М.; Петренко, Д. І.; Васильковський, О. М.; Лещенко, С. Н.; Петренко, Д. И.; Васильковский, А. М.; Leshchenko, S.; Salo, V.; Petrenko, D.; Vasylkovskyi, O. (ЦНТУ, 2018)
В роботі оцінюється вплив конструктивно-технологічних параметрів робочих органів комбінованих глибокорозпушувачів на тяговий опір агрегатів. Доводиться, що використання раціональної формули Горячкіна для аналітичного визначення тягового опору глибокорозпушувачів, у традиційному її представленні є недоречним, оскільки чизельні агрегати здійснюють принципово іншу технологічну операцію порівняно з полицевим плугом. Запропоновано методику визначення тягового опору чизельних знарядь з врахуванням зон деформацій від конструктивних елементів чизельних лап. З практичної точки зору проаналізовано вплив деяких конструктивних елементів глибокорозпушувача на питомий опір ґрунту та проведено оцінку витрати пального в залежності від комплектування агрегату. В работе оценивается влияние конструктивно-технологических параметров рабочих органов комбинированных глубокорыхлителей на тяговое сопротивление агрегатов. Доказывается, что использование рациональной формулы Горячкина для аналитического определения тягового сопротивления глубокорыхлителей, в традиционном ее представлении является неуместным, поскольку чизельные агрегаты осуществляют принципиально иную технологическую операцию по сравнению с отвальным плугом. Предложена методика определения тягового сопротивления чизельных орудий с учетом зон деформаций от конструктивных элементов чизельных лап. С практической точки зрения проанализировано влияние некоторых конструктивных элементов глубокорыхлителя на удельное сопротивление почвы и проведена оценка расхода топлива в зависимости от комплектации агрегата. The influence of structural and technological parameters of operating elements of combined deep tillers on the ploughing resistance of the components has been assessed in the article. The objective of the work is to study the influence of the structural and technological parameters of the operating elements of a deep tiller on the ploughing resistance and the estimation of fuel consumption, depending on the configuration of the unit and the set of operating elements during the operation of the combined chisel assemblies. It has been proved that the application of Goryachkin’s rational formula for the analytical determination of the ploughing resistance of deep tillers, in its traditional presentation, is inappropriate, since chisel components undertake a fundamentally different technological operation in comparison with the moldboard plow. The methodology of identification of the ploughing resistance of chisel devices, taking into account deformation zones from constructive elements of chisel tips, was suggested. We received the equation of the resistance of a chisel operating element with the direct stand and additional horizontal deformers, taking into account normal forces, frictional forces, speed of the machine and tractor assembly, and other factors. On the basis of the experimental data, the influence of some structural elements of the deep tiller on the specific resistance of soil was analyzed and the fuel consumption has been estimated depending on the assembly of the device.
Влияние конструктивно-технологических параметров рабочих органов глубокорыхлителя на тяговое сопротивление
Influence of Structural and Technological Parameters of the Operating Elements of a Deep Tiller on Ploughing Resistance
Keywords: тяговий опір; раціональна формула Горячкіна; чизельний глибокорозпушувач; додаткові деформатори; витрати пального; тяговое сопротивление; рациональная формула Горячкина; чизельный глубокорыхлитель; дополнительные деформаторы; расход топлива; ploughing resistance; Goryachkin’s rational formula; chisel deep tiller; additional deformers; fuel consumption